Outcome after operative treatment of proximal humeral fractures in elderly patients = Outcome nach operativer Versorgung von Humeruskopffrakturen beim älteren Menschen - Muhm, Markus Joachim; Winkler, Hartmut (Zeitschrift für Gerontologie und Geriatrie, 2016)
Background: The proximal humeral fracture (PHF) (5 %) of the elderly is the third most common fracture after proximal femoral and distal radius fractures. Proximal femoral fractures often lead to a loss of autonomy. Objectives: The aim of this study is to show how PHF changes the patient’s autonomy and the coping with everyday life as well as which factors influence the outcome 1 year (y) after surgery. Materials and methods: Data of 62 patients with surgical treatment of a PHF ≥ 60 y was prospectively collected. With a telephone interview Short Form (SF) 12 (physical and mental health; PH, MH), Barthel Index (BI), range of motion, pain, and satisfaction was observed after 3 and 12 months. The dependence of outcome on different factors was investigated. Results: The mean age was 73.3 y (median 73, 60-94). Mortality after 3 months was 3 % and after 1 y 11 %. The PH before the injury (47.9) was significantly better than after 3 months (37.1) and after 1 y (42.6). The MH showed no difference. The BI before the injury (92) was significantly better than after 3 months (86), but the same after 1 y (91). After 1 y > 50 % were able to abduct and flex the arm > 90°. More than two-thirds were able to perform everyday life activities for body care and nutrition after 1 y. Approximately, 73 % of the patients had little or no pain, and 84 % were satisfied with the result after 1 y. Good score values before the fracture resulted in better outcome. Higher severity in fracture led to a higher level of pain. Discussion: A surgically treated PHF in the elderly does not lead to a relevant impairment in quality of life. Despite the lack of complete retrieval of range of motion patients achieve a good to very good result in coping with everyday life.
Gesehen am 26.08.2019
Published online: 29 September 2015